Mary at the Center of Latin American Evangelization.: The Place of the Virgin in the pastoral reflection of Monsignor Farrell (Teología, 2023)
The founding evangelization of Latin America had as its main protagonist the Immaculate Virgin Mary, landed by the Spanish missionaries and constituted as a pastoral agent par excellence. The causes are many, but, above all, we must recognize her unique capacity to assimilate into the culture of peoples and give an inculturated face to the Church. The reflection of Monsignor Gerardo Tomás Farrell addresses this historical-pastoral question. Executive Secretary of the Episcopal Pastoral  Commission (COEPAL) between 1967 and 1972, his thought draws on the wisdom of the main Argentine theologians who contemplated the maternal presence of the Virgin at the root of popular culture, among them Lucio Gera and Rafael Tello. Farrell’s specific contribution to Argentine and Latin American theological-pastoral reflection, from Marian centrality, can nourish the current pastoral guidelines and help to care for the memory of the people, their historical rationality and their deep sense of transcendence.